2016
DOI: 10.1080/19406940.2016.1189954
|View full text |Cite
|
Sign up to set email alerts
|

The State and management of partnership arrangements in France: an analysis of the implementation of the ‘Sport, Health and Well-being’ plan

Abstract: International audienceIn France, the national ‘Sport, Health, and Well-being’ programme (Programme sport, santé, bien-être – PSSBE) aims to develop an active way of life in a country where physical inactivity is becoming increasingly prevalent. While its implementation is based on an inter-ministerial approach whereby responsibility is given to the local government personnel of the Ministry of Sport and the Ministry of Health, numerous studies have shown that the complexity of the State machine and the compart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 31 publications
0
3
0
2
Order By: Relevance
“…From these competencies, municipalities have the authority to influence the conditions and the environment where people live; it is a particularly suitable level to promote an active and healthy lifestyle [20,21]. Studies on national HEPA policies also highlighted the importance of the local level [22,23]. To this end, municipalities play a major role in implementing intersectoral policies for HEPA promotion [4].…”
Section: Introductionmentioning
confidence: 99%
“…From these competencies, municipalities have the authority to influence the conditions and the environment where people live; it is a particularly suitable level to promote an active and healthy lifestyle [20,21]. Studies on national HEPA policies also highlighted the importance of the local level [22,23]. To this end, municipalities play a major role in implementing intersectoral policies for HEPA promotion [4].…”
Section: Introductionmentioning
confidence: 99%
“…This work adds empirical findings on the outcomes of coaches' health promotion activities across the lifespan, reinforcing the rationale that these activities are beneficial not only to youth but also to adult sports experiences and health. Moreover, these results emphasise the role sports clubs can play in public health (Honta, 2016), not only by increasing physical activity (Kokko et al, 2019) but also by embracing the settings-based approach (Kokko, 2014b) to consider sports participants' health in a holistic way (Geidne et al, 2019;Johnson et al, 2019). As this research demonstrated, coaches' health promotion activities should be tailored to participant age, gender and type of sports in order to produce the greatest perceived benefits.…”
Section: Resultsmentioning
confidence: 68%
“…In an effort to go beyond sports or physical activity provision, multiple authors (Geidne et al, 2019;Kokko et al, 2015b), as well as the European Commission's (2007) White Paper on Sport, have argued that sports have the potential to develop health promotion, which could lead to even better sports experiences and health (Van Hoye et al, 2016). In France specifically, policy makers launched the Plan Sport Santé Bien-être (Sport, Health and Well-being) (Honta, 2016) to better link sports and public health.…”
Section: Introductionmentioning
confidence: 99%
“…La territorialisation des politiques de santé fait débat (Amat-Roze, 2011) car elle questionne la légitimité de l'autorité chargée d'articuler entre eux les différentes strates de son gouvernement. Si le « territoire » est consacré comme l'échelle où se révèlent et se traitent les problèmes publics par la mobilisation et la coordination des autorités responsables (Duran, Thoenig, 1996 ;Schweyer, 2004 ;Honta, 2016), la régulation politique du secteur de la santé suppose la production de règles tendant à organiser l'action collective et à lui conférer un sens politique. En région, ce rôle d'animation et d'intégration des initiatives est confié aux agences régionales de santé (ARS).…”
Section: Abstract: Cities -Government -Health -Legitimacy -Metropolitunclassified
“…Cette posture confirme plus généralement qu'un paysage procédural ainsi fragmenté place les élus locaux à l'interface de divers réseaux d'action publique qu'ils sont seuls à même d'articuler, au sein d'administrations ministérielles s'organisant elles-mêmes selon des priorités sélectives. Les services déconcentrés ou agences de l'État restant généralement soucieux de préserver leur position, leur autonomie d'action et leur réseau dans l'espace régional (Moquay, 2009 ;Epstein, 2013 ;Honta, 2016), la régulation politique de la santé est ainsi mise à l'épreuve d'organisations publiques défendant la primauté et la pertinence de leurs dispositifs contractuels respectifs : ASV versus CLS. Une telle posture rappelle aussi que la métropole ne se fait pas uniquement par le haut, sous l'impulsion des visées réformatrices de l'État (Olive, 2015).…”
Section: Territoires De Proximité Contre Territoire Métropolitainunclassified